Aggression, impulsivity and inflammatory markers as risk factors for suicidal behavior. (November 2018) - Coryell, William; Wilcox, Holly; Evans, Simon J.; Pandey, Ghanshyam N.; Jones-Brando, Lorraine; Dickerson, Faith; Yolken, Robert
Abstract: Background: Increased inflammatory markers have been linked to suicidal behavior in numerous studies. Measures of aggression and of impulsivity also comprise risks factors for suicidal behavior and there is evidence that inflammatory markers correlate with these traits. The following analyses compare suicide attempters and non-attempters to determine whether inflammatory markers mediate relationships between aggression or impulsivity and proclivities to suicidal behavior. Methods: Investigators at three academic centers recruited patients in major depressive episodes who had a history of two or more suicide attempts (n = 79), or who had no history of suicide attempts (n = 123). Analyses compared these groups by five inflammatory marker levels and by measures of aggression and of impulsivity. Results: These results did not confirm the hypotheses that cytokine levels would explain relationships between aggressive behavior and suicide attempt history. However, scores for aggressive behavior and for impulsivity were significantly higher among suicide attempters. One of five of the inflammatory markers, (IL-1β), distinguished the two groups with lower values in the suicide attempt group. IL-1β levels correlated inversely with measures of aggression but neither impulsivity or aggressive behavior appear to explain the association between IL-1β levels and suicide attempt status. Conclusion: These results identify recent aggressive behavior, higher levels of impulsivity, and lower levels of IL-1β as risk factors for a history of multiple suicide attempts in a group suffering from major depressive episodes. These measures appear to be additive in their effects.